Inside BAR (The Biblical archaeology review, 1982)
In this issue of BAR, two renowned Israeli scholars, Yigael Yadin and Abraham Malamat, bring their formidable talents to bear on a much-debated Biblical subject—the Israelite takeover of Canaan. "Is the Biblical Account of the Israelite Conquest of Canaan Historically Reliable?" by Yadin and "How Inferior Israelite Forces Conquered Fortified Canaanite Cities" by Malamat […]